Korelasi Antara Perencanaan Pembelajaran Dengan Hasil Belajar Di SMPI Baburrohmah Mojosari Mojokerto 2017-2018 - Mas’ulil Munawaroh; Abdul Muhaimin (Nazhruna: Jurnal Pendidikan Islam, 2019)
In order to realize a quality learning process, it requires professional teachers, especially in planning learning which is teacher preparation before implementing the learning process when the learning process takes place. Planning is determining what will be done. Planning contains a series of broad decisions and explanations of objectives, determination of policies, determination of programs, determination of specific methods and procedures and determination of activities based on daily schedules. This research took place at the Baburrohmah SMPI, Jurangsari Hamlet, Middle Hemisphere Village, Mojosari District, Mojokerto Regency. The type of research in this study is included in quantitative and qualitative research. The technique used to collect data on whether the teacher prepares a learning plan well in the teaching and learning process is a questionnaire (questionnaire) that has previously been tested for validity and reliability according to the standards. Subsequent data analysis was carried out with the help of the SPSS version 22.0 computer program to determine the level of contribution between independent variables and bound and histogram. Based on the results of data analysis regarding the relationship of learning planning with student learning outcomes, it can be concluded that: there is a relationship between learning planning with learning outcomes of class VIII students of SMPI Baburrohmah but very low and not significant. This is evidenced by the value of r-count (0.145) ranging from 0,000 to 0.200, and r-count (0.145) is smaller than r-table (0.254) at a significant level a = 0.05. The magnitude of the relationship (Coefficient of Determination) between Learning Planning (variable X1), with Learning Outcomes (variable Y) class VIII Baburrohmah SMPI in 2016/2017 amounting to 02.11%, the remaining 91.89% is influenced by other factors.